Flux growth and characteristics of cubic boron phosphide - Nwagwu, Ugochukwu (Kansas State University, 2012)
Boron phosphide, BP, is a III-V compound semiconductor with a wide band gap of 2.0 eV that is potentially useful in solid state neutron detectors because of the large thermal neutron capture cross-section of the boron-10 isotope (3840 barns). In this study, cubic BP crystals were grown by crystallizing dissolved boron and phosphorus from a nickel solvent in a sealed (previously evacuated) quartz tube. The boron - nickel solution was located at one end of the tube and held at 1150°C. Phosphorus, initially at the opposite end of the tube at a temperature of 430°C, vaporized, filling the tube to a pressure of 1–5 atmospheres. The phosphorus then dissolved into solution, producing BP. Transparent red crystals up to 4 mm in the largest dimension with mostly hexagonal shape were obtained with a cooling rate of 3°C per hour. The crystal size decreased as the cooling rate increased, and also as growth time decreased. The characterization with x-ray diffraction (XRD) and Raman spectroscopy established that the BP produced through this method were highly crystalline. The lattice constant of the crystals was 4.534 Ǻ, as measured by x-ray diffraction. Intense, sharp Raman phonon peaks were located at 800 cm[superscript]-1 and 830 cm[superscript]-1, in agreement with the values reported in the literature. The FWHM for XRD and Raman spectra were 0.275° and 4 cm[superscript]-1 which are the narrowest ever reported and demonstrates the high quality of the produced crystals. Energy dispersive x-ray spectroscopy (EDS) and scanning electron microscope (SEM) also confirmed the synthesized crystals were cubic BP crystals, with a boron to phosphorus atomic ratio of 1:1. Defect selective etching of BP at 300ºC for two minutes with molten KOH/NaOH revealed triangular and striated etch pits with low densities of defects of ~4 x 10[superscript]7 cm[superscript]-2 and 9.2 x 10[superscript]7 cm[superscript]-2 respectively. The BP crystals were n-type, and an electron mobility of ~39.8 cm[superscript]2/V*s was measured. This is favorable for application in neutron detection. Scaling to larger sizes is the next step through gradient freezing and employing a larger crucible.
Keywords: Flux growth; Solution growth; Neutron detector; Defect selective etching; Nickel solvent; Boron phosphide; Chemical Engineering (0542); Electrical Engineering (0544); Materials Science (0794)